“I always have to look attractive, but nobody cares on what I feel”: Aesthetic labor on Sales Promotion Girl (SPG) - Savira, Pingkan Sekar (Jurnal Sosiologi Dialektika, 2024)
Aesthetic labor is a job that involves the display of aesthetic body appearance and emotions by the workers. Aesthetic labor practices are performed by service workers who interact directly with customers, including Sales Promotion Girls (SPGs). This qualitative research aims to reveal how aesthetic labor practices are carried out by SPGs and what burdens that they carry. A total of 10 SPG informants who have at least one year of work experience were involved. This research found that SPGs always have to maintain their body appearances and emotions to attract customers’ attention and convince them to make purchases. They even spend money to maintain their body appearances, such as for buying healthy foods, cosmetics, skincare products, and going to the salon. SPGs are also expected to always display positive emotions in any situation. Furthermore, SPGs often experience sexual harassment at the workplace. It can be concluded that while performing aesthetic labor practices, SPGs actually experience the practices of being a docile body too. In addition, SPGs have a double burden, namely physical and emotional burdens, in doing their jobs. However, there are still many who underestimate SPGs and ignore the difficulty they face as aesthetic labor workers.